2019
DOI: 10.3892/ijo.2019.4676
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200b and -301 are associated with gemcitabine response as biomarkers in pancreatic carcinoma cells

Abstract: Chemotherapy resistance (congenital or acquired) is one of the principal challenges for the treatment of pancreatic carcinoma. Recent evidence has demonstrated that epithelial to mesenchymal transition (EMT) is associated with chemoresistance in pancreatic carcinoma cells. However, the molecular mechanism underlying the development of chemoresistance remains unknown, and limited therapeutic options are available. Therefore, to anticipate individual chemosensitivity or acquired chemoresistance for patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Based on pilot studies, we have chosen LD20 gemcitabine concentration, which proved to be 200-times higher for Panc1 than for Capan1, which is in line with the higher GEM resistance of Panc1 cell line [29]. Similar to our earlier published results [22], a 60-min mEHT-treatment induced significant apoptosis in FIGURE 5 | Cell cycle analysis for Capan1 and Panc1 cell lines 24 and 48 h after mEHT treatment.…”
Section: Discussionsupporting
confidence: 57%
“…Based on pilot studies, we have chosen LD20 gemcitabine concentration, which proved to be 200-times higher for Panc1 than for Capan1, which is in line with the higher GEM resistance of Panc1 cell line [29]. Similar to our earlier published results [22], a 60-min mEHT-treatment induced significant apoptosis in FIGURE 5 | Cell cycle analysis for Capan1 and Panc1 cell lines 24 and 48 h after mEHT treatment.…”
Section: Discussionsupporting
confidence: 57%
“…Wang et al validated the role of miR-30a in PC sensitization to gemcitabine (10). Another study reported that gemcitabineresistant cells exhibited upregulated miR-301 expression and downregulated gemcitabine-induced apoptosis (11).…”
Section: Introductionmentioning
confidence: 97%
“…Gemcitabine is widely used in advanced pancreatic carcinoma. MiR-200b and miR-125a-3p are revealed to improve chemosensitivity via reversing EMT [131,132], while miR-301 mediates gemcitabine resistance and induces EMT through downregulating cadherin 1 in pancreatic tumor cell lines [131]. In OS, DDP resistance can be alleviated by miR-340 via targeting ZEB1 [133], and miR-233 via forming the miR-233/Hsp70/JNK/JUN/ miR-233 feedback loop [134].…”
Section: Other Cancersmentioning
confidence: 99%